Maintaining continuity of clinical operations while implementing large-scale filmless operations...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Honea R; Mensch B (Journal of Digital Imaging)
Texas Children's Hospital is a pediatric tertiary care facility in the Texas Medical Center with a large-scale, Digital Imaging and Communications in Medicine (DICOM)-compliant picture archival and communications system (PACS) installation. As our PACS has grown from an ultrasound niche PACS into a full-scale, multimodality operation, assuring continuity of clinical operations has become the number one task of the PACS staff. As new equipment is acquired and incorporated into the PACS, workflow processes, responsibilities, and job descriptions must be revised to accommodate filmless operations. Round-the-clock clinical operations must be supported with round-the-clock service, including three shifts, weekends, and holidays. To avoid unnecessary interruptions in clinical service, this requirement includes properly trained operators and users, as well as service personnel. Redundancy is a cornerstone in assuring continuity of clinical operations. This includes all PACS components such as acquisition, network interfaces, gateways, archive, and display. Where redundancy is not feasible, spare parts must be readily available. The need for redundancy also includes trained personnel. Procedures for contingency operations in the event of equipment failures must be devised, documented, and rehearsed. Contingency operations might be required in the event of scheduled as well as unscheduled service events, power outages, network outages, or interruption of the radiology information system (RIS) interface. Methods must be developed and implemented for reporting and documenting problems. We have a Trouble Call service that records a voice message and automatically pages the PACS Console Operator on duty. We also have developed a Maintenance Module on our RIS system where service calls are recorded by technologists and service actions are recorded and monitored by PACS support personnel. In a filmless environment, responsibility for the delivery of images to the radiologist and referring physician must be accepted by each imaging supervisor. Thus, each supervisor must initiate processes to verify correct patient and examination identification and the correct count and routing of images with each examination. Copyright (c) 1999 by W.B. Saunders Company